Inovasi Olahan Durian - Waryono Waryono (Universitas Negeri Padang, 2018)
Kenagarian Barung Barung Belantai Selatan District of Koto XI Tarusan an expansion in 2009 villages of the parent Kenagarian Barung Barung Belantai. This area has a huge agricultural potential such as gambier plant, nutmeg, clove, rubber especially durian abundant. The abundance of this potential can be seen along the road Padang to Painan, many traders durian, and this is the main attraction for people who come to visit the Pesisir Selatan. Visitors would stop by for a taste of durian famous delicious and sticky. Each harvest durian fruit durian abundance so that the selling price is sometimes cheaper. Not to mention the cost of transport to bring durian harvest from the farm/plantation residents require huge costs. As a result, residents sometimes let alone durian harvest wasted. State University of Padang conducted training for mothers of households made into various processed durian cake durian and wingko durian. Wali local village residents can expect to process durian become typical food and souvenirs from this area so as to increase family economy and to support the development of the tourism of Pesisir Selatan.